2016
DOI: 10.1007/s00204-016-1785-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress caused by a SOD1 deficiency ameliorates thioacetamide-triggered cell death via CYP2E1 inhibition but stimulates liver steatosis

Abstract: We investigated the responses of mice that are defective in the superoxide-scavenging enzyme SOD1 to thioacetamide (TAA)-induced hepatotoxicity. When a lethal dose of TAA (500 mg/kg) was intraperitoneally injected, the wild-type (WT) mice all died within 36 h, but all of the SOD1-knockout (KO) mice survived. Treatment with an SOD1 inhibitor rendered the WT mice resistant to TAA toxicity. To elucidate the mechanism responsible for this, we examined the acute effects of a sublethal dose of TAA (200 mg/kg) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…We next performed Oil Red O staining of liver sections in these mice to characterize the intracytoplasmic vacuolar structures ( Figure 3(a) ). The results clearly showed the accumulation of larger numbers of lipid droplets in Sod1 −/− mouse livers than in WT mouse livers, consistent with previous reports [ 8 , 9 , 28 ], while no difference was found between Prdx4 −/y mouse livers and WT mouse livers. In the case of the DKO mouse livers, the numbers of lipid droplets were enhanced considerably compared to Sod1 −/− mouse livers.…”
Section: Resultssupporting
confidence: 91%
“…We next performed Oil Red O staining of liver sections in these mice to characterize the intracytoplasmic vacuolar structures ( Figure 3(a) ). The results clearly showed the accumulation of larger numbers of lipid droplets in Sod1 −/− mouse livers than in WT mouse livers, consistent with previous reports [ 8 , 9 , 28 ], while no difference was found between Prdx4 −/y mouse livers and WT mouse livers. In the case of the DKO mouse livers, the numbers of lipid droplets were enhanced considerably compared to Sod1 −/− mouse livers.…”
Section: Resultssupporting
confidence: 91%
“…This experimental model mimics the physiopathogenic and pathophysiological aspects of the disease in humans and helps in the understanding of its progress and the possibility of therapeutic intervention [16,[27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these findings, we found that maltol treatment significantly increased SOD and CAT levels in D‐Gal‐induced accelerated senescence and significantly reduced MDA levels. The cytochrome P450 enzyme system, mainly CYP2E1, is involved in the metabolism of endogenous and exogenous substances (Shirato, Homma, Lee, Kurahashi, & Fujii, 2017; Ye et al, 2012). Even though there was no additional increase in the CYP2E1 levels in aged WT mice, the increased levels of oxidative stress in WT mice could have been produced through CYP2E1‐mediated metabolism of endogenous substrates throughout the life span (Abdelmegeed, Choi, Ha, & Song, 2017).…”
Section: Discussionmentioning
confidence: 99%